The Scottish National Party transition to power - Mitchell, James, 1960-; Bennie, Lynn G.; Johns, Robert, 1975- (Oxford : Oxford University Press, 2012)
Based on a survey of the entire membership and over 80 elite interviews, 'The Scottish National Party' provides a comprehensive account of the nature of the SNP following its election as a party of government for the first time in its 80-year history.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Scottish National Party; Nationalism -- Scotland